Evolution des teneurs en carbone organique et azote dans les matieres en suspension des eaux de surface d'un petit bassin versant agricole sur pente dans le Nord Vietnam - Phan, Ha Hai An; Orange, Didier; Huon, S.; Henry des Tureaux, Thierry; Pham Van Rinh; Tran, Thi My Linh; Podwojewski, Pascal (2007)
This study deals with the organic carbon concentration and nitrogen concentration inside the suspended particulate matter transported by the small rivers with a watershed area below 10 ha and totally enclosed on sloping lands. The scientific purpose is to determine if these two components of soil losses from erosion process on topsoil could be used as tracers for the organic matter to point out the surface water pathway during one peak flow. The fluctuations in POC content, in C/N rate and in ?13C isotopic rate are no linked with the vegetation species on the sloping land during the process of surface runoff until the runoff collect in the small stream. However their absolute values are characteristic of each kind of vegetation cover. Then our results allow assuming that the mix of chemical tracers such as pH, water conductivity, organic carbon and nitrogen content in sediment with the associate measurements of ?13C isotopic component can be used to analyze the surface water pathway within a small sloping watershed during one peak flow. The next step will be the calculation of hydrological components of the hydrogram in relationship with the water pathway by the mixed equation use applied to the ?13C isotopic component of the organic matter form the sediments and from their corresponding soils.